Adaptive capabilities and productive potential of initial material from peas (Pisum sativum) - KOSEV, VALENTIN; VASILEVA, VILIANA (The Indian Journal of Agricultural Sciences, 2019)
The productivity of crops is related to their adaptive potential to the soil and climatic conditions of the environment. In this work the adaptive properties of seven pea (Pisum sativum L.) varieties were studied on the root length, dry root mass weight, number of nodules and number of leaves/plant. The study was conducted in 2014-2016 in the experimental field of the Institute of Forage Crops, Pleven, Bulgaria. Peas varieties in the complex of proanalyzed characteristics can be distributed as follows: Wt6803 combines high stability (bi = 1.04, 0.54), homeostaticity (Hom = 9.43, 40.96) and productivity (54.11, 73.42) by number of nodules and number of leaves/plant. The variety Mir has high values of the studied traits and was characterized by the same high degree of both, plasticity and stability. X07P54, X06PWY, NDPO80138-B-2 and CA1P were stable (bi <1) and showed high homeostasis for most signs but are low productive. L020140 had a mean expression of the signs and was sensitive to changes in environmental conditions (bi> 1) by number of leaves per plant and dry root mass weight. The varieties Wt6803, Mir and L020140 represent a specific selective value by number of nodules (43.34, 7.51, 15.81) and number of leaves/plant (57.87, 62.57, 27.54) and can be used to create new genetic diversity, and the selection should be not only aimed at increasing the upper productivity threshold but also at the lower.